1991
DOI: 10.1161/01.res.68.5.1471
|View full text |Cite
|
Sign up to set email alerts
|

Vagal stimulation and prevention of sudden death in conscious dogs with a healed myocardial infarction.

Abstract: The interest for the antifibrillatory effect of vagal stimulation has been largely limited by the fact that this concept seemed restricted to acute experiments in anesthetized animals. To explore the potentially protective role of vagal stimulation in conscious animals we developed a chronically implantable device to be placed around the cervical right vagus. An anterior myocardial infarction was produced in 161 dogs; 1 month later an exercise stress test was performed on the 105 survivors. Toward the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
350
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 600 publications
(374 citation statements)
references
References 78 publications
12
350
0
12
Order By: Relevance
“…In autonomically-intact dogs, spontaneous ischaemia-induced VF increased in vivo following i.v. atropine (Goldstein et al 1973), with similar conclusions drawn from control experiments in the dog model of SCD (Schwartz et al 1984;Vanoli et al 1991). This is supported by data during direct VNS where atropine abolished protection (Yoon et al 1977).…”
Section: Nitric Oxide (No) and Apd Restitutionsupporting
confidence: 71%
See 3 more Smart Citations
“…In autonomically-intact dogs, spontaneous ischaemia-induced VF increased in vivo following i.v. atropine (Goldstein et al 1973), with similar conclusions drawn from control experiments in the dog model of SCD (Schwartz et al 1984;Vanoli et al 1991). This is supported by data during direct VNS where atropine abolished protection (Yoon et al 1977).…”
Section: Nitric Oxide (No) and Apd Restitutionsupporting
confidence: 71%
“…The seminal work by Schwartz and his group provided insight in the association between autonomic tone and arrhythmic death in a conscious canine model of sudden ischaemic cardiac death. It was found that concomitant vagus nerve stimulation significantly prevented ischaemia-induced VF (Vanoli et al 1991). Of equal significance, it was found that baseline baroreflex sensitivity was high in animals resistant to VF and low in susceptible animals .…”
Section: Autonomic Nervous System and Sudden Cardiac Deathmentioning
confidence: 94%
See 2 more Smart Citations
“…In animals, electrical stimulation of the cervical vagus nerve has been shown to evoke cardiovascular effects, for example by lowering the ventricular fibrillation threshold (Brack et al, 2013). Moreover, VNS is known to reduce incidence of ventricular arrhythmias and mortality during ischemia (Brack et al, 2013) and prevent sudden cardiac death in dogs with myocardial infarction (Vanoli et al, 1991). VNS has also been investigated in animal models of chronic heart failure, a condition characterised by a sustained increase in sympathetic drive and a concurrent withdrawal of parasympathetic activity (Triposkiadis et al, 2009).…”
Section: Anatomy Of the Auricular Branch Of The Vagus Nervementioning
confidence: 99%